Formulation And In Vitro, In Vivo Evaluation of Colon Targeted Drug Delivery System Of 5-Fluorouracil - S, Subimol.; Pathan, Amjadkhan A. (International Journal of Membrane Science and Technology, 2023)
Colon-targeted drug delivery systems can provide therapeutic benefits including better patient compliance and lower costs. The present investigation is aimed to design a colon specific microbially triggered system using biodegradable co-polymer mixtures. The calibration curves of 5-FU were measured in distilled water, 0.1N HCl and phosphate buffer of pH 6.8 and 7.4 which showed good linearity. Compatibility study of pure drugs, excipients and their physical mixtures were evaluated and passed as per standards. Solubility determination was carried out in different solvents. Satisfactory results were found from evaluation of micromeritic parameters such as flow property, in-vitro dissolution study and kinetic study. The prime focus of the study was to design and evaluate a swelling dependent delayed release system for a colonic delivery of anticancer agent 5-Fluorouracil (5-FU) and further to determine the effects of carboxy polymer (Carbopol 71G-NF) on release behavior of 5-FU from a matrix tablet system containing different amounts of inulin (a biodegradable oligofructose) aiding in enzymatic degradation by colonic microflora. Mixed film coating with a blend of Ethyl cellulose: Eudragit®S-100 (2:1) at coat weight levels of 2%w/w, 4%w/w and 6.0%w/w was carried out respectively, which further retarded the drug release in the initial hours of the in-vitro dissolution profile. Swelling studies were also carried out on uncoated matrix tablet batches. The releases studies with or without rat cecal contents were performed on optimized batches and the samples were analyzed by a validated RP-HPLC method. In-vitro rat cecal study results revealed that complete drug release would occur from the tablets in the human colonic microenvironment. The study revealed an effective site-specific delivery of a hydrophilic chemotherapeutic agent, 5-FU to the colon for the treatment of various local as well as systemic pathologies.